Factors Affecting Market Demand on Sports Fields Rental Business In Medan - Ismu Hartarto Julianto; Fauzi Arif Lubis (Agregat: Jurnal Ekonomi dan Bisnis, 2022)
The sports field is of course much needed by the community, especially sports lovers, especially futsal and badminton. Ofcourse this affects the concept of market demand in the sports field rental business which must pay attention to the high and low market demand and the demand in the market is different.The purpose of this research is to determine the factors that influence the field rental business based on the theory of demand in the city of Medan. The selected factors are price (X1), Location (X2), Consumer Satisfaction (X3). This study uses quantitative methods by using data and numbers that are processed again using the SPSS 25 application to find results and conclusions from the research. The total sample of respondents taken is 55 people according to the number of futsal and badminton field owners in Medan City. The results show that all factors such as price, location, and customer satisfaction always affect the demand for the sports field rental market.